"My English Is Its Own Rule": Voicing a Translingual Sensibility through Poetry. Issue 5 (2nd September 2020) - Seltzer, Kate
ABSTRACT: As part of an ethnographic study of a secondary English Language Arts classroom, one teacher took a critical translingual approach to curriculum and instruction, encouraging students to engage in translanguaging and to explore the intersections of language with power and identity. The larger study's central question was, what does participation in a critical translingual English curriculum bring up about students' identities and ideologies in relation to language? Guided by this question, this article details a series of lessons that featured a spoken word poem in which the author used English to reflect on her relationship to Spanish and asked students to explore their language practices in their own writing. This article illustrates that while students' poems expressed an apparent internalization of deficit language ideologies, they also expressed resistance to those very ideologies through the voicing of a translingual sensibility.